Assessing student learning in sport event management through reflective practice: Measure of success in co-curricular learning in higher education - STRAUGHAN, Paulin Tay (Institutional Knowledge at Singapore Management University, 2018)
Co-curricular activities are an integral part of students’ holistic education. Yet, assessing experiential learning outcomes in the co-curricular space can sometimes prove to be challenging, given that not all of such learning experiences are designed or structured in a manner similar to academic courses or programmes. Rather, indirect measures of learning such as asking students to reflect on what they have learnt and experienced is often used for rendering visible learning outcomes. Using reflective practice, the SMU Gravical 2018, an international sporting event, provided the learning platform for the 19 committee members of the Singapore Management University (SMU) Climb team. Their reflections were examined using Bradley’s Criteria for assessing levels of reflection and then coded based on the P-O-L-C management framework. The framework helped us understand how students learnt from their experiences, the processes of sport event management, including managing logistics, branding, sponsorships and stakeholders. Our analyses of students’ reflections and focus group discussion demonstrated heightened awareness and deeper understanding towards personal and team management, systems and processes and socio-emotional skills.